2015
DOI: 10.1038/ncomms9885
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neural and physiological phenotyping of a single human

Abstract: Psychiatric disorders are characterized by major fluctuations in psychological function over the course of weeks and months, but the dynamic characteristics of brain function over this timescale in healthy individuals are unknown. Here, as a proof of concept to address this question, we present the MyConnectome project. An intensive phenome-wide assessment of a single human was performed over a period of 18 months, including functional and structural brain connectivity using magnetic resonance imaging, psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
352
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(385 citation statements)
references
References 70 publications
16
352
0
2
Order By: Relevance
“…Researchers continue to take seriously the effort to systematically measure the factors that influence test/ retest reliability of responses across time and tasks, and these sorts of studies are increasingly common [83][84][85][86][87][88] . Other research programs focus on addressing questions about the long-term within-subject stability of responses [89][90] , and how the accurate assessment of within-participant differences might address questions about individual differences 93 . There is increasing support for conducting and publishing the results of confirmatory studies [94][95] , thereby rectifying some existing biases that often favor the publication of new, novel results over confirmatory ones.…”
Section: Results Reproducibilitymentioning
confidence: 99%
“…Researchers continue to take seriously the effort to systematically measure the factors that influence test/ retest reliability of responses across time and tasks, and these sorts of studies are increasingly common [83][84][85][86][87][88] . Other research programs focus on addressing questions about the long-term within-subject stability of responses [89][90] , and how the accurate assessment of within-participant differences might address questions about individual differences 93 . There is increasing support for conducting and publishing the results of confirmatory studies [94][95] , thereby rectifying some existing biases that often favor the publication of new, novel results over confirmatory ones.…”
Section: Results Reproducibilitymentioning
confidence: 99%
“…Further, while the neurobiological basis of inter-individual variability is coming into increasing focus, we still know relatively little about how individual brains change over time (intra-individual variability) [23]. Likewise, the relevance of lab-based measures of self-control (to take one relevant example) for predicting individual variability in real-world behavior remains largely unclear.…”
Section: Enter: Neuropredictionmentioning
confidence: 99%
“…The molecular profiles of well-being phenotypes can also be studied in a dynamic approach over a period of months, because phenotypes like well-being are likely also to be characterized by short-and medium-term molecular fluctuations of molecular networks. This concept has recently been applied to a single participant who was characterized in-depth over the period of 532 days for dynamics of brain function and their relation to psychological and biological parameters (Poldrack et al 2015). Molecular profiles related to well-being can also serve as endpoints in intervention studies for promoting happiness, as recently shown for a Yoga intervention that was able to reduce inflammation-related biomarkers among fatigued breast cancer survivor (Irwin et al 2014) and family dementia care givers (Black et al 2013).…”
Section: A First Research Question Is About Molecular Profiling Of DImentioning
confidence: 99%